2022
DOI: 10.1111/ina.13018
|View full text |Cite
|
Sign up to set email alerts
|

Combining adaptive and heat balance models for thermal sensation prediction: A new approach towards a theory and data‐driven adaptive thermal heat balance model

Abstract: The adaptive thermal heat balance (ATHB) framework introduced a method to account for the three adaptive principals, namely physiological, behavioral, and psychological adaptation, individually within existing heat balance models. This work presents a more detailed theoretical framework together with a theory‐driven empirical determination toward a new formulation of the ATHBPMV. The empirical development followed a rigor statistical process known from machine learning approaches including training, validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The data that has been obtained for analysis from each hypothesis was percentages of hours of comfort temperature and energy demand depending on the set-point temperature established in Table 3. With regard to thermal comfort, the results of the interior temperature in free evolution were analysed according to the adaptive comfort methodology [61,62] defined by the European Standard EN 16798-1:2019 "Energy performance of buildings. Ventilation for buildings.…”
Section: Discussionmentioning
confidence: 99%
“…The data that has been obtained for analysis from each hypothesis was percentages of hours of comfort temperature and energy demand depending on the set-point temperature established in Table 3. With regard to thermal comfort, the results of the interior temperature in free evolution were analysed according to the adaptive comfort methodology [61,62] defined by the European Standard EN 16798-1:2019 "Energy performance of buildings. Ventilation for buildings.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid outliers, research [25] and [44] set a minimum sample size for each analyzed group, but extreme values in normal groups were not addressed. The method of inspection was used in research [45] to filter out unexpected values, but it would require too much labor when the sample size is large. The Boxplot rule was used in research [38] and [26] to select outliers, but a more systematic view of different outlier removal approaches in the thermal comfort domain has yet to be discovered.…”
Section: Global Thermal Comfort Database IImentioning
confidence: 99%
“…In thermal comfort studies, outlier detection is usually involved in data preprocessing to remove the misleading effects of extreme values. The available techniques include stochastic-based methods like the 3-Sigma rule [72], the Boxplot rule [73], and the Hampel rule [74]; distance-based methods such as cook distance [75] and k-nearest neighbour (KNN) [76]; manually inspection [45] or setting fixed ranges [77]; and binning or adjusting variables into specific intervals [78]. The majority of studies in thermal comfort research filtered outliers using stochastic-based methods, and more details can be found in Appendix B.…”
Section: Brief Review Of Outlier Detection Techniquesmentioning
confidence: 99%